2015
DOI: 10.5301/tj.5000402
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated Whole-Breast Radiotherapy and Concomitant Boost after Breast Conservation in Elderly Patients

Abstract: Aims To report the 5- and 10-year results of accelerated hypofractionated whole-breast radiotherapy (WBRT) with concomitant boost to the tumor bed in 83 consecutive patients with early breast cancer aged >70 years. Methods All patients were treated with breast conservation and hypofractionated WBRT. The prescription dose to the whole breast was 45 Gy (2.25 Gy/20 fractions) with an additional daily concomitant boost of 0.25 Gy to the surgical cavity (2.5 Gy/20 fractions up to 50 Gy). The maximum detected toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
0
17
0
1
Order By: Relevance
“…[11][12][13]22 In terms of acute toxicity, 47% presented with grade 1 radiodermatitis, and 53% did not exhibit any toxicity. [25][26][27][28][29][30][31][32] Chronic toxicity was evaluated after 6 months, and 6 patients developed grade 1 toxicity (telangiectasias and fibrosis). Good cosmesis was present in 82%, which is very similar to that reported by Formenti et al 13,19,20 as well as the results from studies that have involved HF and concomitant boost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13]22 In terms of acute toxicity, 47% presented with grade 1 radiodermatitis, and 53% did not exhibit any toxicity. [25][26][27][28][29][30][31][32] Chronic toxicity was evaluated after 6 months, and 6 patients developed grade 1 toxicity (telangiectasias and fibrosis). Good cosmesis was present in 82%, which is very similar to that reported by Formenti et al 13,19,20 as well as the results from studies that have involved HF and concomitant boost.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29][30] Regarding patients over 70 years of age who have been treated with this schedule, the evidence is scarce, but the results have proven this approach to be an option for this population group. 20,[31][32][33][34][35] The 2018 management guides of the National Comprehensive Cancer Network (NCCN) indicate that boost to the tumour bed is indicated for those who are <50 years of age and have high-grade or focally positive margins. The boost to positive margins requires an increase of the dose to the tumour bed and may increase fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Doré et al (27) and Cante et al (25) revealed that whole-breast HF after breast-conserving surgery is a safe and efficient approach for elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…DISCUSSIONCosmetic results scored in both arms after 12 month were excellent/good in 83.4% of patients and fair/poor in 16.7%, whereas superiorly, Cante et al reported cosmetic results were excellent in 69% of patients, good in 22%, fair in 5% and poor in 4%(21). Cante et al, as well in 2017, reported results of excellent/good in 87.8% of patients and fair/poor in 12.2%…”
mentioning
confidence: 92%
“…The concomitant delivery of the TB boost along with WBRT further reduces OTT, with an eventual ulterior gain (7,14). The results of retrospective studies of hypofractionated radiotherapy in early breast cancer suggest satisfactory outcomes in terms of tumour control and late adverse effects (15)(16)(17), this applies when modest increases in fraction size are combined with consequent and appropriate downward adjustments of the total dose (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%